Absorption, Distribution and Excretion of Four Forms of Titanium Dioxide Pigment in the Rat. Issue 8 (16th June 2017) - Farrell, Thomas P.; Magnuson, Berna
Abstract: Titanium dioxide (TiO2 ) is a white color additive that has a long history of global approval and use in food. There is, however, considerable confusion regarding the applicability of the biological effects of novel, engineered, nano‐sized forms of TiO2 developed for nonpigmentary applications to the safety of oral exposure to food grade TiO2 pigment. The objective of this study was to assess the absorption, distribution, and routes of excretion in rats after oral exposure to food grade TiO2 . Four different grades of TiO2 (200 ppm) or control (0 ppm) diets were fed to rats for 7 consecutive days, followed by control diet only for 1, 24, or 72 h. Concentrations of titanium in liver, kidney and muscle were mainly below the limit of detection (<0.1 to < 0.2 mg/kg wet weight); tissue concentrations of titanium above the LOD were in the range of 0.1 to 0.3 mg/kg wet weight for all groups. Whole blood concentrations of titanium were <0.04 mg/L for all groups. Urinary excretion of titanium was equivalent to <2% daily dose/L of urine for all groups and was generally below the limit of quantification (<0.04 mg/L). Feces represented the predominant route of excretion. These results demonstrate that there is no accumulation of titanium in tissues following consumption of diets containing 200 ppm food grade TiO2 . No differences in systemic absorption of the 4 forms of TiO2 were observed indicating that the bioavailability of TiO2 is consistently low for the range of particle sizes and morphologies examined in this study.